Uji Kuat Tekan Mortar Geopolymer Berbasis Fly Ash dan Kapur - Tupail, Fharhan; Jasman, Jasman; Muis B, Abd (Jurnal Ilmiah Rekayasa Sipil, 2025)
The increasing use of infrastructure in Indonesia every year requires a large cement supply. Cement is a very crucial material for development, and its demand in increasing line with the development of human facilities and infrastructure. However, the cement manufacturing process can cause air pollution, CO₂ gas emissions, and produce B3 waste that can damage the environment. One way to reduce this environmental impact is to utilize industrial waste, such as fly ash and lime, as an alternative to cement using geopolymer technology. This study aimed to measure the compressive strength of geopolymer mortar made from fly ash and lime, and to understand how variations in the mixture affect the achievement of maximum mortar strength. The approach applied in this study is an experimental method carried out in the laboratory of the Muhammadiyah University of Parepare. The test specimens used were in the form of cubes measuring 5x5x5 cm with a ratio of fly ash and lime of 70:30, 75:25, and 80:20, so that a total of 36 test specimens were made. The experiment results showed that the mixture with a higher proportion of ash consistently produced greater compressive strength. The mixture with 75% fly ash and 25% lime increased in compressive strength from 6.667 MPa after 7 days to 10.667 MPa after 28 days. This proves that the addition of fly ash in greater amounts can increase the compressive strength of the mortar, especially because fly ash functions as a pozzolanic material that reacts with free lime, forming calcium silicate hydrate (C-S-H) compounds that function as the main binder and thus strengthen the mortar structure. Therefore, the combination of fly ash and lime at 80%:20% is the most efficient and superior mixture in producing high-strength mortar.